Modeling of three-dimensional motion of deformable droplets in stokes regime using boundary element method - Abramova, Оlga Aleksandrovna; Itkulova, Yulia Аyratovna; Gumerov, Nail Asgatovich (Computational Continuum Mechanics, 2013)
The paper presents three-dimensional modeling of the dynamics of droplets under the imposed ambient flow in an unbounded domain and a cylindrical channel at low Reynolds numbers using the boundary element method. The obtained results for test cases are compared with the analytical solution for the flow around a single droplet. The inclination angle of drops and their deformation in a shear flow are studied at various parameters. Computational results are compared with experimental and numerical data found in the literature and with the analytical solution within the framework of small strain theory. The problem statement for the periodic motion of droplets in a channel of arbitrary cross-section is developed. Computations of the dynamics of deformable drops of different volumes and arbitrary distribution in a flow are performed.
Keywords: emulsion channel flow; boundary element method; deformable droplets; Stokes equations